Adamantinoma: A clinicopathological review and update - Ranjan Prabhat; Vasishta Rakesh K; Jain Vijay K; Jain Deepali; Kumar Yashwant (BMC, 2008)
Abstract Adamantinoma is a primary low-grade, malignant bone tumor that is predominantly located in the mid-portion of the tibia. The etiology of the tumor is still a matter of debate. The initial symptoms of adamantinoma are often indolent and nonspecific and depend on location and extent of the disease. Histologically, classic adamantinoma is a biphasic tumor characterized by epithelial and osteofibrous components that may be intermingled with each other in various proportions and differentiating patterns. To assure the histological diagnosis, pathologists should employ immunohistochemistry for demonstrating the sometimes sparse epithelial cell nests when the radiological features are suggestive of adamantinoma. There is paucity of compiled data over adamantinoma in the literature, hence authors tried to make a comprehensive review which must be of use to beginners and trained pathologists. Our objective is to further define the clinicoradiologic features and pathologic spectra of adamantinoma.